Not Academic Enough? Enjoyment of Physical Education and the Arts and School Engagement in Early and Middle Adolescence (¿Suficientemente académico? Disfrute de la Educación Física y las Artes e implicación del estudiante con la escuela en la adolescenci - Garcia Bengoechea, Enrique; Lorenzino, Lisa; Gray, Shirley (Retos, 2019)
Abstract. School engagement during adolescence is an important personal asset for youth development. While multiple factors contribute to student engagement at school, research on the role of curricular factors is scarce. Based on a secondary analysis of data from Cycle 3 of the National Longitudinal Survey of Children and Youth, this study examined the associations of Canadian students’ enjoyment of arts education, language arts, mathematics, physical education, and science with their engagement at school during early and middle adolescence, accounting for relevant demographic, family, peer, school, and community factors. All things considered, high levels of enjoyment of physical education and arts education were among the top factors making a contribution to school engagement in both periods of adolescence, and enjoyment of physical education was actually the strongest contributor to school engagement in early adolescence. The findings suggest that curricular factors, and in particular the quality of students’ experiences in physical education and arts education, may be more important than previously recognized in terms of understanding and promoting school engagement in early and middle adolescence. Specifically, the findings provide initial evidence that a positive experience in physical education and arts education can contribute to student engagement and valuing of school. In addition, the findings provide further support for the role of participation in extracurricular activities and after school programs in fostering a sense of connectedness to and endorsement of school values and outcomes during the developmental periods considered. Resumen. La implicación con la escuela durante la adolescencia es un importante activo personal para el desarrollo humano. Sin embargo, la investigación sobre el rol de factores curriculares es escasa. A partir de un análisis secundario de datos del Ciclo 3 de la Encuesta nacional del desarrollo de los niños y los jóvenes, este estudio examina las asociaciones del disfrute de las Artes, las Lenguas, las Matemáticas, la Educación Física y las Ciencias con la implicación escolar en estudiantes canadienses durante la adolescencia temprana y media, teniendo en cuenta factores demográficos, familiares, sociales, escolares y comunitarios relevantes. Niveles altos de disfrute de la Educación Física y de las Artes fueron dos de los factores que más contribuyeron en este estudio a la implicación escolar durante la adolescencia temprana y media, mientras que el disfrute de la Educación Física se reveló específicamente como el factor más importante en la adolescencia temprana. Factores curriculares, y en particular la calidad de la experiencia de los alumnos en las asignaturas de Educación Física y de Artes, pueden ser más importantes que lo pensado anteriormente para comprender y promover el compromiso con la escuela durante la adolescencia temprana y media. Los resultados proporcionan evidencias iniciales de que una experiencia positiva en las asignaturas de Educación Física y de Artes puede contribuir a un mayor compromiso con la escuela y una valoración favorable de la misma por parte de los alumnos y refuerzan el rol de la participación en actividades extracurriculares y programas fuera del horario escolar.